Un encuentro morfofonológico insólito: los sufijos diminutivos del español y las marcas internacionales - Gaál, Zoltán Kristóf (Acta Hispanica, 2017)
In this article we will examine a somewhat strange and still unexplored area of Spanish morphophonology. It is a well-known fact that the use of evaluative (and particularly the diminutive) suffixes enjoys a great vitality in today’s Spanish. Their vitality is reflected by the regular and productive character of the application of the process. It has also been demonstrated that the choice between the allomorphs of the diminutive suffixes is governed by welldefined phonological principles. But what happens when native speakers must leave behind their linguistic routine and have to add a diminutive suffix to words that they rarely would summit to this mechanism (namely, international brand names)? The article displays a pioneer approach to the question with particular focus on analogy and concludes that while the suffixation of the brand names that end in a phonotactically natural segment is somewhat less consistent than the suffixation of Spanish words with the same ending, those of exotic ending do show certain degree of coherence with the rest of the system.